Resilience and Quality of Life on Type 2 Diabetes Mellitus Patients with Chronic Complications - Nur Widayati; Izdihar Javier Wardika; Akhmad Zainur Ridla (Nursing and Health Sciences Journal (NHSJ), 2024)
The emergence of complications in patients with type 2 DM significantly impacts the quality of life. Resilience as part of self-coping may be connected with the quality of life and the severity of the complications. This study analyzed the correlation between resilience and quality of life in type 2 DM patients with chronic complications. The method was an observational study with a cross-sectional approach. Thirty-five respondents were recruited in this study using a consecutive sampling technique. Data were collected using Connor Davidson Resilience Scale 25 (CD-RISC 25) and Diabetes Quality of Life (DQOL) questionnaires and analyzed by Pearson Product Moment (p <0.05). The result showed that the mean value of resilience was 63.06 (±12.47), while the average value of quality of life was 72.46 (±11.78). A strong positive correlation existed between resilience and quality of life (p-value = 0.000; r = 0.782). Increased resilience score equals increased quality of life of type 2 DM patients with chronic complications. Providing interventions to increase resilience is essential to optimize the quality of life in type 2 DM patients with chronic complications.